Rightly Dividing the Word of Truth Recent Reference Works in Religious Studies - Johnson, Wendell G. (2018)
Several useful multi-volume reference works have been published during the past 2 years. This review essay profiles several of these resources and introduces them to theological librarians and their patrons.
Keywords: Christianity (United States); War and religion; Arts and religion; religion and history; Rezension